Concept «Imperative» as a basis of grammatical category of the imperative mood (Eurasian Journal of Philology Science and Education, 2015)
In linguistics there is an opinion according to which certain concept lies at the basis of grammatical category. Concept is a result of conceptualization and categorizations of reality and unites received information in the generalclasses. The categorization becomes available to understanding according to language. Language represents external and internal worlds of the person as system of categories. The main to language categories are presented in grammar. The purpose of this paper is define, what values and meanings of a concept the IMPERATIVE makes it a basis ofgrammatical category of an imperative mood.
Keywords: concept; imperative; imperative mood; sememes; basis; grammatical category